2010
DOI: 10.1007/s10567-010-0064-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Verbal Threat Information in the Development of Childhood Fear. “Beware the Jabberwock!”

Abstract: Rachman’s (Behaviour Research and Therapy 15:372–387, 1977; Clinical Psychology Review 11:155–173, 1991) three pathways theory proposed that childhood fears not only arise as a consequence of direct learning experiences, but can also be elicited by means of threat information transmission. This review looks at the scientific evidence for this idea, which has accumulated during the past three decades. We review research on the influences of media exposure on children’s fears, retrospective parent and child repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 130 publications
(218 reference statements)
10
134
0
2
Order By: Relevance
“…Consistent with previous reviews (i.e., Muris and Field 2010), which have distinguished between the cognitive and behavioral components of fear based on established theoretical models (see Lang 1968Lang , 1985Merckelbach et al 1996), we have distinguished between studies that examined fear beliefs and anxious behaviors specifically and those that examined anxiety symptoms more generally.…”
Section: Evidence From Studies Of Community Populationssupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with previous reviews (i.e., Muris and Field 2010), which have distinguished between the cognitive and behavioral components of fear based on established theoretical models (see Lang 1968Lang , 1985Merckelbach et al 1996), we have distinguished between studies that examined fear beliefs and anxious behaviors specifically and those that examined anxiety symptoms more generally.…”
Section: Evidence From Studies Of Community Populationssupporting
confidence: 79%
“…Where previous reviews have considered the role of parental verbal communication of fear-relevant information in child anxiety, they have typically included studies that examined nonverbal parenting behavior (e.g., Fisak and Grills-Taquechel), or studies in which parents were not the source of fear-relevant information (e.g., Muris and Field 2010). Furthermore, previous reviews have typically included studies that used a broad range of methods, including both observations of actual parent verbal communication and measures of child or parent perceived verbal communication, on the basis of (sometimes retrospective) child-or parent-report questionnaires (e.g., Fisak and Grills-Taquechel 2007;Rapee 2012), making it difficult to draw conclusions on what is actually being measured.…”
mentioning
confidence: 99%
“…Contemporary theorists postulate vicarious or alternative pathways to fear and anxiety (e.g., Field, 2006;Mineka & Oehlberg, 2008;Muris & Field, 2011) that appear to be based on direct conditioning processes (e.g., Bouton, Mineka, & Barlow, 2001;Mineka & Oehlberg, 2008). Others have considered the top-down influence of high-level cognitive processes Lovibond & Shanks, 2002;Mitchell et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…From a slightly different perspective, a growing body of research has shown that older children are able to learn to fear a novel stimulus following overt, verbal expression about its dangerous qualities (Muris and Field 2010). As with the research on modelling, the assumption is that anxious parents will express more threat and danger when describing objects and experiences and this, in turn, will lead to fear acquisition among their children.…”
Section: Modellingmentioning
confidence: 99%